Model Agroforestry yang Diterapkan Kelompok Tani Hutan (KTH) Berbasis Agribisnis di Desa Ulusaddang Kabupaten Pinrang - Saleh, Muh Ikmal; Ariandi, Rahmat (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2023)
This study aimed to identify the Agroforestry model applied by the Agribusiness-based KTH in Ulusaddang Village, Pinrang District, South Sulawesi. Determination of the sample using the census method involving KTH, which represents the entire population, namely KTH Sipatuo and KTH Chulande Sipatuo. The results showed that the agroforestry models applied to each KTH were agro silviculture, agrosilvofishery, agro silvopasture, and monoculture (non-agroforestry). Several types of commodities and livestock that make up the agroforestry system are 1) Woody plants; sugar palm (Arenga pinnata), candlenut (Aleurites moluccanus), white teak (Gmelina arborea), mahogany (Swietenia macrophylla L), cinnamon (Cinnamomum verum), 2) seasonal plants; corn (Zea mays), banana (Musa paradisiaca L), avocado (Persea Americana), durian (Durio), cocoa (Theobroma cacao), robusta coffee (Coffea canephora), 3) animal feed; lamtoro (Leucaena leucocephala), gamal (Gliricidia sepium), 4) Livestock; Cattle (Bos taurus sp), and tilapia (Oreochromis niloticus).